DETERMINASI NON PERFORMING FINANCING PADA BANK UMUM SYARIAH DI INDONESIA - Noerlela Sari; Ellyana Amran (Media Ekonomi, 2019)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Inflation, and Gross Domestic Product (GDP) on Non Performing Financing (NPF) on Islamic Commercial Banks in Indonesia for 2012-2016 Period. The research method used in this study is quantitative research methods. The sample is 8 Sharia Commercial Banks which were previously determined by the purposive sampling method. Data collected in the form of quarterly financial reports for each Sharia Bank from 2012-2016. The analysis technique used is panel data regression. The results showed that the Capital Adequacy Ratio (CAR) and Gross Domestic Product (GDP) had a negative and significant effect on Non Performing Financing (NPF) at Islamic Commercial Banks while the inflation and Financing to Deposit Ratio (FDR) variables had a negative and not significant effect on the level Non Performing Financing (NPF) at Islamic Commercial Banks.